2020
DOI: 10.1002/bab.1866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenolic compounds from the rind of Punica granatum on the activity of three metabolism‐related enzymes

Abstract: Enzyme activity modulation by synthetic compounds provide strategies combining the inhibitory and therapeutic mode of action of the confirmed inhibitors. However, natural modulators could offer a valuable alternative for synthetic ones for the treatment of different chronic diseases (diabetes, hypertension, cancer) due to the numerous side effects of the latter. In vitro screening assays were conducted for Punica granatum rind methanolic extract against three metabolism‐related enzymes: α‐amylase, tyrosinase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Table 1 contains the detailed information about 27 plants and agricultural wastes that were extracted in methanol and investigated for their inhibitory activity against α-amylase, tyrosinase, and hyaluronidase (results are not included). Among the 27 plants extracts, Punica granatum results were illustrated in our previous publication [58] and it was concluded that Punica granatum extract and some of its fractions exhibited multitarget inhibition against α-amylase, tyrosinase, and hyaluronidase along with quercetin. In this study, we aim to illustrate the multitarget inhibition of P. guajava (guava) for the same target enzymes.…”
Section: Discussionmentioning
confidence: 83%
“…Table 1 contains the detailed information about 27 plants and agricultural wastes that were extracted in methanol and investigated for their inhibitory activity against α-amylase, tyrosinase, and hyaluronidase (results are not included). Among the 27 plants extracts, Punica granatum results were illustrated in our previous publication [58] and it was concluded that Punica granatum extract and some of its fractions exhibited multitarget inhibition against α-amylase, tyrosinase, and hyaluronidase along with quercetin. In this study, we aim to illustrate the multitarget inhibition of P. guajava (guava) for the same target enzymes.…”
Section: Discussionmentioning
confidence: 83%